Hayy Ibnu Yaqdzhan: The Concept of Knowledge Development from Ibn Tufail's Perspective and His Contribution to Islamic Education - Ichsan, Yazida; Salsabila, Unik Hanifah; Husna, Difa'ul; Okfia, Supitri (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
The purpose of the article Hayy Ibnu Yaqdzhan: The Concept of Development of Knowledge from Ibn Tufail's Perspective and His Contribution to Islamic Education is twofold. First, a description of the growth of knowledge from Ibnu Thufail's viewpoint. Second, understanding the relevance of Hayy's love story to epistemology and Islamic education. Through documentation, this study examines the novel by Hayy Ibnu Yadzhan through a content analysis of the text. The findings of this study indicate that Hayy Ibnu Yadzhan's novel contributes to the creation of an epistemology of knowing in Islam in which knowledge can be attained through the use of the senses, reason, and intuition. In addition, Hayy's new contribution to Islamic education includes three essential components. First, about cognitive growth. Roman Hayy describes the development process as sensory, imitative, exploratory, philosophical, contemplative, and mystical. Second is the concept of knowledge, which can be acquired through sense, reason, and intuition. Third, in terms of religiosity, all the positive elements in the form of beliefs, rituals, religious knowledge, and religious experience always lead to the essence and wisdom.   Keywords: Hayy Ibn Yaqdzhan, Ibn Thufail, Islamic Education.